UNFOLDING FLESH TOWARDS THE OTHER: LEVINAS’ PERSPECTIVE OF MATERNITY AND THE FEMININE - Poleshchuk, Irina (Problemos, 2013)
The paper discusses a formation of the ethical body in Levinas’ philosophy. The central question is how different modalities of subjectivity, brought into light in face-to-face relation with the other, constitute a particular ethical and sensible embodiment. The main topics of the paper are caress, touch, and pain, and their role in constructing ethical embodiment. The focus is given to such existential modalities as being-in-one’s-own-skin, the-one-for-the-other and having-the-other-under-one’s-own-skin. The conceptual work of maternity and the feminine in the face-to-face situation accentuate a meaning of responsive and responsible sensibility which Levinas reveals in his major works Otherwise than Being or Beyond the Essence and Totality and Infinity. Keywords: Emmanuel Levinas, sensibility, embodiment, flesh, face, the other, skin, caress, touch, pain, maternity, feminine Atveriant kūną kitam: leviniškoji motinystės ir moteriškumo interpretacija Irina Poleshchuk Santrauka Straipsnyje analizuojamas etinis kūnas Levino filosofijoje. Pagrindinis klausimas – kaip skirtingi subjektyvybės modalumai, išnirę į šviesą betarpiškoje akistatoje su Kitu, įsteigia konkretų etinį ir juslinį įkūnytumą. Pagrindinės straipsnio temos yra glamonė, lietimas ir skausmas bei jų vaidmuo kuriant etinį įsikūnijimą. Dėmesys skiriamas tokiems egzistenciniams modalumams kaip „buvimas savo paties odoje“, „vienas kitam“, „kito buvimas po mano oda“. Motinystės ir moteriškumo konceptualinis veikimas akistatos situacijoje išryškina reikšmę atsakančio ir atsakingo juslumo, kurį Levinas atskleidžia savo pagrindiniuose darbuose „Kitaip negu būtis, arba anapus esmės“ ir „Totalybė ir begalybė“. Pagrindiniai žodžiai: Emmanuel Levinas, juslumas, įkūnytumas, kūnas, veidas, kitas, oda, glamonė, lietimas, skausmas, motinystė, moteriškumas.